Vehicle Currency Pricing and Exchange Rate Pass-Through - Natalie Chen; Wanyu Chung; Dennis Novy (Center for Economic Studies and ifo Institute (CESifo), 2019)
Using detailed firm-level transactions data for UK imports, we find that invoicing in a vehicle currency is pervasive, with more than half of transactions in our sample invoiced in neither sterling nor the exporter's currency. We then study the relationship between invoicing currency choices and the response of import prices to exchange rate changes. We find that for transactions invoiced in a vehicle currency, import prices are much more sensitive to changes in the vehicle currency than in the bilateral exchange rate. Pass-through therefore substantially increases once we account for vehicle currencies. Our results help to explain the higher-than-expected pass-through into import prices during the Great Recession and after the EU referendum. Finally, within a theoretical framework we conceptualize an omitted variable bias arising in estimating pass-through with only bilateral exchange rates under vehicle currency pricing. Overall, our results contribute to understanding the disconnect between exchange rates and prices.
Keywords: F14; F31; F41; 330; CPI; dollar; euro; exchange rate pass-through; inflation; invoicing; sterling; UK; vehicle currency pricing